2017
DOI: 10.18203/2320-1770.ijrcog20175300
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic pain due to intrauterine retention of fetal bone after second trimester medical termination of pregnancy: a rare case report

Abstract: Intrauterine retention of fetal bone is a rare complication of second trimester termination of pregnancy. These patients may present with abnormal uterine bleeding, dysmenorrhea and secondary infertility. In this case pelvic pain was the only symptom. A 32-year-old woman with history of second trimester medical termination of pregnancy was examined. Pelvic ultrasound revealed retained products of conception. After surgical evacuation, intrauterine retained fetal bone was identified to be the cause of pelvic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Since bones can act as an intra-uterine contraceptive device, infertility is the most common reported symptom. Therefore, despite its rarity, this condition should be considered as a cause of secondary infertility (5). Based on literature, these cases have been mainly discovered in low educated and low socioeconomic classes of societies and in areas with inadequate health care facilities (6).…”
Section: Discussionmentioning
confidence: 99%
“…Since bones can act as an intra-uterine contraceptive device, infertility is the most common reported symptom. Therefore, despite its rarity, this condition should be considered as a cause of secondary infertility (5). Based on literature, these cases have been mainly discovered in low educated and low socioeconomic classes of societies and in areas with inadequate health care facilities (6).…”
Section: Discussionmentioning
confidence: 99%
“…Other cases presented with pelvic pain, vaginal discharge and, abnormal uterine bleeding. [8][9][10] In their global, comprehensive, and systematic review on IUBF, Khan et al 11 reviewed 293 cases reported between the years 1928 and 2013. In this study, the mean ± SD age at presentation was 32.7 ± 8.9.…”
Section: Discussionmentioning
confidence: 99%